PENDEKATAN SAMR DALAM PENDIDIKAN AGAMA ISLAM - Ainurahmah, Annisa; Umami, Nashwa; Rosyada, Maida Fatma; Anjalina, Dita; Salsabila, Unik Hanifah (Jurnal Al-Fatih, 2025)
The SAMR (Substitution, Augmentation, Modification, Redefinition) approach is a framework that helps educators integrate technology in the learning process. In the context of Islamic Religious Education (PAI), this approach can be used to improve the quality of learning, encourage student engagement, and create learning experiences that are relevant to the times. This article aims to explain and describe the systematic stages of SAMR in Islamic Education learning through literature analysis and case studies. In the Substitution stage, technology is used as a substitute for traditional learning tools, such as replacing books with Quran e-books. The Augmentation stage introduces additional features, such as interactive applications that provide tafsir and tajweed. In the Modification stage, project-based learning is supported with online collaboration through learning platforms. The Redefinition stage allows the creation of learning experiences that were previously impossible, such as virtual simulations of Islamic history or cross-country discussions on global Islamic issues. The results showed that the implementation of SAMR can improve students' understanding of Islamic education materials, develop 21st century skills, and strengthen spiritual values.